Pengukuran Koordinasi Mata dengan Tangan Siswa Kelas V melalui Tes Lempar Tangkap Bola Tenis dan Memukul Bola yang dijatuhkan di SD Muhammadiyah 1 Panji - Wahed Dussawal (STKIP AL HIKMAH SURABAYA, 2022)
This research is based on the importance of using simple media in knowing students' eye coordination through the throwing and catching baseball tests and hitting the dropped baseball tests. This research is a descriptive qualitative approach with a field trial survey method with a total of 27 students from class V SD Muhammadiyah 1 Panji. Data collection using instruments in the form of eye coordination measurement tests on each student in turn, students are given the opportunity to throw then catch the ball and hit the dropped ball 5 times. Based on the results of the research, it is known that the eye coordination ability through the throwing and catching ball test mostly has a very poor category with an average value of 2.40, while the results of the eye coordination test through the ball hitting baseball test have a very poor category with an average value of 1 ,6, therefore there is a need for special training that emphasizes the eye-hand coordination of students.